In vitro activity of dalbavancin against Gram-positive bacteria isolated from diabetic foot osteomyelitis. (11th April 2021) - Pantel, Alix; Nachar, Oriane; Boudet, Agathe; Loubet, Paul; Schuldiner, Sophie; Cellier, Nicolas; Sotto, Albert; Dunyach-Remy, Catherine; Lavigne, Jean-Philippe
Abstract: Background: Diabetic foot infections (DFIs) represent a serious threat to public health because of their frequency and the severity of their consequences, i.e. osteomyelitis and amputation. The management of diabetic foot osteomyelitis (DFOM) requires prolonged antibiotic therapy. In Western countries, Gram-positive bacteria are the most commonly encountered pathogens. Objectives: This study evaluated the in vitro activity of dalbavancin, a novel lipoglycopeptide with extended half-life, recently marketed in Europe for acute bacterial skin and skin structure infections, on a panel of Gram-positive bacteria responsible for DFOM. Methods: Dalbavancin activity was evaluated against a panel of Gram-positive bacterial strains isolated from bone biopsies performed by a trained surgeon among patients with suspected DFOM. MICs were determined using MIC Test Strips (Liofilchem) and confirmed with the EUCAST broth microdilution method. Three other antimicrobial agents (vancomycin, teicoplanin and ceftobiprole) were used as comparators. Results: Dalbavancin showed excellent activity against all Gram-positive bacterial strains tested, including one teicoplanin-resistant Staphylococcus epidermidis isolate. With MIC50 and MIC90 values of 0.047 and 0.094 mg/L, respectively, dalbavancin showed the most potent in vitro activity among antimicrobial agents tested. Conclusions: With its efficacy, good tolerability and unique pharmacokinetic properties, dalbavancin appears to be a promising treatment for DFOM involving Gram-positive bacteria.